A NATIONWIDE PREVALENCE STUDY AND RISK FACTORS FOR HEPATITIS A, B, C AND D INFECTIONS IN TURKEY - Tozun, Nurdan; Ozdogan, Osman C.; Cakaloglu, Yilmaz; Idilman, Ramazan; Karasu, Zeki; Akarca, Ulus S.; Kaymakoglu, Sabahattin; Ergonul, Onder (WILEY-BLACKWELL, 2010)
61st Annual Meeting of the American-Association-for-the-Study-of-Liver-Diseases, Boston, MA, OCT 29-NOV 02, 2010